Atypical Vancouver B1 periprosthetic fracture of the proximal femur in the United Kingdom: a case report challenged by myeloma, osteoporosis, infection, and recurrent implant failures - Sayantan Saha; Azeem Ahmed; Rama Mohan (Journal of Trauma and Injury)
The indications for total hip replacement are increasing and not limited to osteoarthritis. Total hip replacement may also be done for trauma and pathological fractures in patients otherwise physiologically fit and active. This trend has led to an inevitable rise in complications such as periprosthetic femoral fracture. Periprosthetic femoral fracture can be challenging due to poor bone quality, osteoporosis, and stress fractures. We present a case of periprosthetic femoral fracture in a 71-year-old woman with some components of an atypical femoral fracture. The fracture was internally fixed but was subsequently complicated by infection, implant failure needing revision, and later stress fracture. She was on a bisphosphonate after her index total hip replacement surgery for an impending pathological left proximal femur fracture, and this may have caused the later stress fracture. Unfortunately, she then experienced implant breakage (nonunion), which was treated with a biplanar locking plate and bone grafting. The patient finally regained her premorbid mobility 13 months after the last surgery and progressed satisfactorily towards bony union.